The Effect of System Digitalization and Work Discipline on Employee Performance in the Business Operation Support Department of PT. Huawei - Kusjono, Gatot; Srirezeki, Ayu (Jurnal Ilmiah Sumber Daya Manusia, 2025)
This study examines how the digitalization of systems and work discipline affects employee performance in the Business Operation Support Department of PT Huawei Indonesia. Using a quantitative survey method of 100 respondents, the analysis was carried out through linear regression with SPSS version 29. The findings showed that the digitization of the system had a significant effect (t=16.461>1.984; p=0.001) with the equation Y=8.186+1.293X1. Work discipline had a stronger impact (t=19.151>1.984; β=0.578; equation Y=2.353+1.703X2). Simultaneously, both variables contributed significantly (F=228.574>3.090; R²=82.5%; equation Y=-1.389+0.548X1+1.108X2), with work discipline as the dominant factor. The research emphasizes the importance of a balance between the implementation of digital technology and strengthening discipline for performance optimization.